The Niulang Staff - A Cowhearding Stick as Weapon - Donald W. Cheung (Universidad de León, 2012)
Yu Qi created the Niulang staff system about 300 years ago. He taught Xiao Side and the art was passed down within the Xiao family to the current grandmaster, Xiao Mingkui. The staff is about 1-meter long and incorporates techniques from both long and short weapons. The concept of yin and yang is central to Niulang staff practice, requiring a proper balance between defense and attack as well as softness and power. The staff always moves in a spiral motion and short explosive power is generated from the waist/kua of the body. Yi (intent) and shen (spirit) are central elements guiding the external movements. The Niulang staff art is designated in China as a major traditional wushu discipline for preservation and research.